Research on the Use of Task-Based Language Teaching Method in English Language Teaching Based on Big Data 5G IoT Scenario. (23rd September 2022) - Xu, Chunjing
Abstract : The state implemented the compulsory education standard for full-time students in 2001, which clearly stipulates that English teachers should promote special language teaching methods, develop comprehensive language use skills, and propose teaching methods such as practice, cooperation, and communication. The task-based language teaching method has become a commonly used method in English teaching, and it is necessary to study the application of task-based language teaching method in English courses and try to apply the task-based language teaching method effectively. This study analyzes the needs of English teaching in the context of big data 5G IoT scenario, new curriculum reform, and theories related to English teaching methods in order to explore new methods of English teaching, verify its feasibility and necessity, and prepare reference materials for future grammar teaching research.